2001
DOI: 10.1093/jnci/93.14.1088
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Membrane Fatty Acids and Subsequent Breast Cancer: a Prospective Italian Study

Abstract: Background:The relationship between erythrocyte membrane fatty acids and postmenopausal breast cancer risk was analyzed previously only by retrospective studies, which suggested a protective effect of increased saturation index (SI), i.e., the ratio of membrane stearic to oleic acid. We investigated the relationships in a prospective study of hormones, diet, and prediagnostic breast cancer (the ORDET study) conducted in northern Italy. Methods: A total of 4052 postmenopausal women were followed for an average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
166
10
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(191 citation statements)
references
References 44 publications
11
166
10
4
Order By: Relevance
“…Therefore, the possibility that the observed association was due to confounding should be considered. In addition, among the seven studies on serum fatty acids and breast cancer, four studies were conducted in Europe, and no association was found between SFA, MUFA, PUFA, n-3 PUFA and n-6 PUFA and risk of breast cancer, except for PUFA [0.31 (0.12-0.77), 37 0.34 (0.15-0.79) 39 ] and n-6 PUFA [0.35 (0.12-0.84)]. 37 In this meta-analysis, positive associations were found between dietary total fat, MUFA and PUFA intake and risk of breast cancer in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the possibility that the observed association was due to confounding should be considered. In addition, among the seven studies on serum fatty acids and breast cancer, four studies were conducted in Europe, and no association was found between SFA, MUFA, PUFA, n-3 PUFA and n-6 PUFA and risk of breast cancer, except for PUFA [0.31 (0.12-0.77), 37 0.34 (0.15-0.79) 39 ] and n-6 PUFA [0.35 (0.12-0.84)]. 37 In this meta-analysis, positive associations were found between dietary total fat, MUFA and PUFA intake and risk of breast cancer in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…1). Finally, 24 independent studies from 23 articles 7,8,[10][11][12][13][14][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] (38,262 cases among 1,387,366 subjects) were included on dietary total fat and fatty acids intake, and seven articles [34][35][36][37][38][39][40] (1,334 cases among 3,511 subjects) were included on serum fatty acids.…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%
“…No association was found in the four studies from the US (Stampfer et al, 1987;Toniolo et al, 1994;Gertig et al, 1999;Holmes et al, 1999). Four cohort studies have explored the marine n-3 fatty acid -breast cancer relationship using biomarkers (prediagnostic serum phospholipids or erythrocyte membranes) (Vatten et al, 1993;Chajes et al, 1999;Pala et al, 2001;SaadatianElahi et al, 2002). Only one of these four studies reported an inverse association between high levels of DHA measured in erythrocyte membranes and breast cancer (P for trend ¼ 0.05) (Pala et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Four cohort studies have explored the marine n-3 fatty acid -breast cancer relationship using biomarkers (prediagnostic serum phospholipids or erythrocyte membranes) (Vatten et al, 1993;Chajes et al, 1999;Pala et al, 2001;SaadatianElahi et al, 2002). Only one of these four studies reported an inverse association between high levels of DHA measured in erythrocyte membranes and breast cancer (P for trend ¼ 0.05) (Pala et al, 2001). The discrepancies among cohort studies may be due to differences in ranges of intake across the various populations.…”
Section: Discussionmentioning
confidence: 99%
“…Yep et al (2002) reported that plasma PL 20:5 n-3 and 22:6 significantly increased in 10 healthy subjects, aged 21-64 y-old, after they consumed fish oil enriched bread for 3 weeks compared with baseline. A number of studies found that dietary 18:0 was positively associated with plasma PL 18:0 concentration despite that membrane 18:0 can be partly converted to 18:1, which is controlled by the enzyme 9-desaturase (Pala et al, 2001). In the ARIC Study, the proportion of SFA and PUFA in plasma cholesterol ester and PL was well correlated with the dietary intake of these fatty acids as assessed by a semiquantitative FFQ (Ma et al, 1995).…”
Section: Discussionmentioning
confidence: 99%